Pengembangan Aplikasi Katalog Perpustakaan Terintegrasi Menggunakan Metode RESTful pada Perpustakaan Kota Semarang dan Perpustakaan Daerah Jawa Tengah - Egia Rosi Subhiyakto; Yani Parti Astuti; Novita Kurnia Ningrum (Politeknik Harapan Bersama, 2018)
Development of technology allows access to information becomes an easy thing to do. Along the way, the majority of agencies, both private and government, have an adequate source of information in the form of website applications. The use of website applications is growing in terms of access to information. It is not unusual that access to the current library catalog more uses an information system. The problem arises when the number of library catalogs that can be accessed but still separate, in the sense of having to move from one website to another website to access the catalog. The existence of web service technology is a solution to connect access one website application with another website. In this research, the library catalog access is integrated. The library is a case study of the library of Semarang City and Central Java Regional Library. The method used in this research is a light RESTful method in resource consumption so that it can be more efficient. The catalog integration application has been successfully built using the PHP programming language and MySQL database. Evaluation results show the application has been built, have a satisfactory performance, easy to use, useful and the majority of users are satisfied to use the application.